RETRACTION NOTICE TO “PID PATH FOLLOWING CONTROL SYSTEM DESIGN ON UNMANNED AUTONOMOUS FORKLIFT PROTOTYPE” [BAREKENG: J. Math. & App., vol. 18(4), pp. 2093-2112, Dec. 2024] - Teguh Herlambang; Hendro Nurhadi; Katherin Indriawati; Reza Maliki Akbar (PATTIMURA UNIVERSITY, 2026)
This article has been retracted: please see Elsevier’s Article Correction, Retraction and Removal Policy (https://www.elsevier.com/about/policies-and-standards/article-withdrawal). This article has been retracted at the request of the Editor-in-Chief and the authors. After publication, the Editorial Office received documented communications indicating concerns about the provenance, authorship/attribution, and permission to publish the content. The journal’s assessment concluded that the published paper exhibits substantial overlap with an earlier academic work (a prior thesis deposited in an institutional repository) and that the reuse/publication of that material was not properly authorized and/or was insufficiently disclosed and attributed during the submission process. These matters fall within circumstances where retraction is appropriate to safeguard the integrity of the scholarly record, including situations involving copyright-related concerns and serious breaches of publication ethics. The retraction is issued to maintain the clarity, transparency, and integrity of the scholarly record. The journal apologizes to readers for any inconvenience caused. All authors have been informed of this retraction and agree to it. Supporting documentation, including signed statements of consent to retract from all authors, is available via a Google Drive folder link that has been provided to the Editorial Office (see documents in this link).